USING FOOTBALL AS A TOOL TO SOLVE SOCIAL PROBLEMS: EXPERIENCE OF INTERNATIONAL PROJECTS (Physical Culture and Sport: Scientific Perspective, 2024)
The authors of the article analyzed the potential opportunities and real implementation of football as a means of solving social problems using the example of international social projects. It is substantiated that the mass of people interested in the development of this sport, its popularity, the media coverage of famous players, as well as the simplicity of the organization led to the fact that football was chosen as a tool in such projects. Yes, the concept "find a social and humanitarian problem in a particular country, form a strategy of actions and solve it by means, in particular football", works. On the example of the project "Active and football-like sports" (Ghana), possible results are given: a) knowledge, skills and abilities formed during it (creating micro-enterprises); b) a real opportunity for creative youth to develop their own business ideas; c) new jobs; d) popularization of football through the sale of football paraphernalia "Active and football sports"; e) creation of a unique product - a soccer ball for difficult playing conditions. Related projects in Georgia and Colombia are analyzed, the goals and objectives of their implementation are highlighted. It has been proven that it is sports events that are "friendly" to children and programs for the protection of their rights. That is, children and representatives of youth remain the object of attention. The activities of the Cross Cultures Association (Denmark), which is currently the main donor of the Open Fun Football Schools project implemented in Ukraine, are illustrated. It was determined that the project is open to everyone and is not aimed at achieving a sports result at any cost, but at getting joy from the game regardless of the level of the child's abilities, introducing the values of a healthy lifestyle for young people, preventing and overcoming children's crime and conflicts, ensuring equal access to football for girls, orphans, children with special needs. active citizens.
Keywords: children; youth; project; social and humanitarian problem; sport; football